Retire – why yes, why not? Results of a study on the Czech seniors - Krejcova, Aneta; Rašticová, Martina (Journal of Eastern European and Central Asian Research (JEECAR), 2020)
Currently, one of the most discussed topics in Europe is population aging and its consequences. Most of the countries have already introduced many measures to support older people but also has changed their retirement age. The amount of people older than 50 is increasing and it is of great importance how this group will be approached on different levels. Retirement is considered as a very important stage of life. Therefore, the need for examination of factors influencing retirement decisions is crucial. In general, there are factors which are similar in every country, but there are also country-specific factors, which are unique. This article focuses on the factors which are significant in the Czech Republic. The analysis is based on data from the SHARE database and the factors are investigated by using the logit model.